1975
DOI: 10.1111/j.1755-3768.1975.tb00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Temperature in Normal Subjects and Arterial Occlusive Disease

Abstract: A direct, thermo-electrical method of corneal temperature recording is presented. The corneal temperature averaged 33.7 degrees C in normal subjects, with no side difference and no difference between the sexes. The various parameters which may influence the corneal temperature are discussed. The technique was applied to groups of patients suffering from either polymyalgia rheumatica, central retinal artery embolism or temporal arteritis. In the latter group of patients a marked drop in corneal temperature was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…It was reported that, OST increases when an eye is infected with anterior uveitis [36,71], and indicates a negative correlation for carotid artery stenosis [19,67,72]. The degree of hyperemia in bulbar conjunctiva (examined in terms of grade of redness using McMonnies scale) were positively correlated to OST [73].…”
Section: Application Of Ir Thermography To Ocular Studiesmentioning
confidence: 93%
“…It was reported that, OST increases when an eye is infected with anterior uveitis [36,71], and indicates a negative correlation for carotid artery stenosis [19,67,72]. The degree of hyperemia in bulbar conjunctiva (examined in terms of grade of redness using McMonnies scale) were positively correlated to OST [73].…”
Section: Application Of Ir Thermography To Ocular Studiesmentioning
confidence: 93%
“…[7][8][9] Under normal conditions, corneal temperature seems to be maintained by heat transfer from the tear film and the limbal vasculature, but primarily from the aqueous humor. 11 When the eye is open, evaporation, convection, and radiation all result in heat loss from the front surface of the eye. 12 During WC application, there is heat transfer directly from the palpebral conjunctiva to the precorneal tear layer and anterior cornea, especially when the conjunctiva is pressed against the cornea and there is an inhibition of heat loss from the anterior surface because the eye is closed.…”
mentioning
confidence: 99%
“…9 The relationship between ocular surface temperature (OST) and room temperature has been well documented. [10][11][12][13] There has been little discussion about the effect of ambient temperature on tear film parameters. Most researchers to date tended to focus on the relationship between OST and ambient temperature, ignoring its effect on tear film parameters and the interrelationship between these parameters.…”
mentioning
confidence: 99%